ARNOLD AND THATCHER: A REPORT ON CONTEMPORARY EDUCATIONAL POLICY - Graham, Robert J. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1989)
Margaret Thatcher's Conservative government is planning legislation to initiate a radical overhaul of the education system in Britain. State schools could begin to break away from Local Education Authority control in late 1989. The ideas of Matthew Arnold on one level demonstrate the advantage of grounding present concerns in their history, and on another level highlight for educationists aspects of the current debate. Two of Arnold's major statements on education are briefly revisited; this is followed by an extended commentary on what Arnold might think of Mrs. Thatcher's current proposals were he alive today. The paper concludes by pointing out the correspondence between nineteenth-century issues and the shape taken by contemporary reality, as weil as how the situation in Britain reflects fundamental notions of perennial relevance for those involved at all levels of education. RÉSUMÉ Le gouvernement conservateur de Mme. Thatcher entend soumettre un projet de loi pour effectuer une refonte totale de l'enseignement en Grande Bretagne. Les écoles d'État devraient commencer à se scinder des authorités locales responsables de l'enseignement (local Education Authority) vers la fin de 1989. En plus de démontrer l'avantage qu'il y a à replacer les préoccupations actuelles dans leur contexte historique, les idées de Matthew Arnold font ressortir pour les spécialistes les points saillants du dossier. L'auteur réexamine brièvement deux déclarations importantes d'Arnold sur le sujet et poursuit en imaginant les réflexions que lui auraient inspirées les propositions de Mme Thatcher, s'il était encore en vie. L'auteur souligne ensuite la corrélation qui existe entre les enjeux du XIXe siècle et la situation actuelle et explique comment la situation qui prévaut actuellement en Grande-Bretagne reflète la pérennité des notions fondamentales pour les protagonistes de l'enseignement à tous les paliers.